2005
DOI: 10.1152/ajpheart.00055.2005
|View full text |Cite
|
Sign up to set email alerts
|

Postconditioning via stuttering reperfusion limits myocardial infarct size in rabbit hearts: role of ERK1/2

Abstract: Emerging evidence suggests that restoration of blood flow in a stuttering manner may limit lethal myocardial ischemia-reperfusion injury. However, the mechanisms contributing to this phenomenon, termed postconditioning (post-C), remain poorly defined. Our aim was to test the hypothesis that activation of classic "survival kinases," phosphatidylinositol 3-kinase (PI3-kinase) and/or extracellular signal-regulated kinase (ERK)1/2, may play a role in post-C-induced cardioprotection. In protocol 1, isolated buffer-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
149
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(174 citation statements)
references
References 33 publications
19
149
0
6
Order By: Relevance
“…These results were also obtained by Darling et al [21] in an experimental study that assessed infarction in rabbit hearts. The IPostC was able to minimize the area of infarction in comparison to the control group, by performing four cycles of ischemia and reperfusion lasting 30 seconds before initiation of the reperfusion phase.…”
Section: Discussionsupporting
confidence: 78%
“…These results were also obtained by Darling et al [21] in an experimental study that assessed infarction in rabbit hearts. The IPostC was able to minimize the area of infarction in comparison to the control group, by performing four cycles of ischemia and reperfusion lasting 30 seconds before initiation of the reperfusion phase.…”
Section: Discussionsupporting
confidence: 78%
“…18 Erk1/2 was very recently also implicated in ischemic postconditioning. 14 Toma et al recently showed that Erk1/2 mediates desflurane-induced preconditioning. 16 The adenosine A 1 /A 2 subtype receptor agonist 5'-(N-ethylcardoxamido) adenosine (NECA) and bradykinin administered during early reperfusion reduced infarct size by activation of Erk1/2 in isolated rabbit hearts.…”
Section: Discussionmentioning
confidence: 99%
“…13 Activation of Erk1/2 has been proposed as a redundant mechanism by which downstream elements of the PI3K-Akt cascade may be stimulated to favourably modulate reperfusion injury. 13 The extracellular signal-related kinases mediate ischemic 14 and pharmacological postconditioning, 10,15 and also play important roles in preconditioning produced by the volatile anesthetic desflurane. 16 Thus, the current investigation tested the hypothesis isoflurane-induced postconditioning is dependent on activation of Erk1/2.…”
Section: Résultats : L'exposition Brève à Une Concentration Alvéolairmentioning
confidence: 99%
“…16 Experimental and clinical studies have indicated the protective effects of postconditioning in ischaemia/reperfusion injury. [17][18][19][20][21] This protection is not only associated with inhibition of inflammation and apoptosis, 22,23 but also with attenuation of oxidative stress. 3,24 The aim of the present study was to use a rat model of ischaemia/ reperfusion injury to evaluate the effects of ischaemic postconditioning on mitochondrial ROS production, in order to determine whether its inhibitory effects on oxidative stress are mediated via the mitochondrial pathway, since the golgi apparatus is also a source of ROS.…”
Section: Introductionmentioning
confidence: 99%